PENYEBAB TAMATAN SMA/SEDERAJAT TIDAK DAPAT MELANJUTKAN KEPERGURUAN TINGGI DI NAGARI AIE TAJUN KECAMATAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Rinova, Devi; Suarto, Edi; Thesiwati, Aslan Sari (Pendidikan Geografi, 2013)
ABSTRACTEducation in believe capable of imparting new capacity for everyone to learn new knowledge and skills so that it can be obtained by human being productive. To create a quality human being must be in bekali with education, good education at school or education outside the school. The purpose of this research is to gain an overview of the causes of the high school graduate/equivalent can not continue to university in view of: 1) the income of the elderly, 2) parent education, 3) interest of the child. And this type of research is qualitative, the subject of this research through a snowball sampling, data collected through: (1) interviews (2) observation, (3) documentation, testing the validity of the data in the study used triangulation techniques, data analysis and valid data. Based on the results of data analysis and discussion conclude things as follows: 1) income parents are one of the causes of his son could not continue to university since there is no cost. 2) parent education does not include the cause of his child does not continue to university. Parents are also paying attention to the importance of education. 3) seen from childs high school graduate/interests equal that there are some children expressed an interest one cause can not continue to university, because the child had no interest. And there are some children expressed an interest does not include the cause could not proceed to university, because children have a high interest but no cost